2020
DOI: 10.1038/s41433-020-01131-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cycloplegia on the ocular biometry and intraocular lens power based on age

Abstract: Background To investigate the effect of cycloplegia on the ocular biometry and intraocular lens (IOL) power in different age groups. Methods This cross-sectional study enrolled 240 right eyes of 240 healthy volunteers. Three groups were formed (range to years; group 1: 50-60, group 2: 30-40 and group 3: 10-20, respectively). We measured keratometry, central corneal thickness (CCT), white-to-white (WtW) distance, anterior chamber depth (ACD), and axial lentgh (AL) both before and after cycloplegia. The IOL powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 32 publications
(74 reference statements)
1
30
0
Order By: Relevance
“…Some studies have reported no signi cant change in keratometry readings following cycloplegia as in the present study [9,11,12,19]. However, the pupil dilation could effect the keratometric readings and corneal attening [13,21] or steeping [26] has been reported in the previous studies after cycloplegia. Although these differences in keratometric readings were statistically signi cant, they were not clinically signi cant in the previous studies.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Some studies have reported no signi cant change in keratometry readings following cycloplegia as in the present study [9,11,12,19]. However, the pupil dilation could effect the keratometric readings and corneal attening [13,21] or steeping [26] has been reported in the previous studies after cycloplegia. Although these differences in keratometric readings were statistically signi cant, they were not clinically signi cant in the previous studies.…”
Section: Resultssupporting
confidence: 55%
“…Tuncer at al. [13] found a signi cant attening by 0.054 D in the mean keraometric reading with AL-Scan in presbyopic eyes aged between 50 and 60 years of age. Cheng and Hsieh [21] proposed that during miosis, the contractive force of ciliary muscles (CMs) acts on the sclera spur where the ciliary body is attached, and the centripetal force of the peripheral cornea steepens the cornea.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations